Analyzing the Indigenous Adaptation in Urban Planning and Architecture of Selected Resort Cities in Vietnam - Nguyen, Viet Huy; Vu, Thi Huong Lan; Do, Dinh Trong (International Journal of Sustainable Construction Engineering and Technology, 2024)
Indigenous adaptation refers to the process by which local communities integrate traditional knowledge, cultural practices, and ecological principles into contemporary systems to respond to social, environmental, and economic challenges.  Globally, there are lots of resort cities which have done quite well with regard to indigenous adaptation in urban planning and architecture. In Vietnam, the French built a number of resort cities during their occupation. These resort cities, with their dual focus on tourism and local community well-being, provide a unique lens to study the interplay between tradition and modernity in urban design. However, these resort cities now face unique challenges due to the interplay of tourism, urban development, and environmental sustainability.Learning lesson collected from selected cases of resort cities in the world, this paper presents the technique to analyze and evaluate the indigenous adaptive level with regard to urban planning and architecture. The technique is accompanied by a set of established criteria (elements) which have been withdrawn from international experience. The technique is then demonstrated with selected resort cities in Vietnam including Tam Dao, Bach Ma, Ba Vi, Sa Pa, Da Lat. Further study can explore more thoroughly the applicability of the technique to other indigenous adaptation situations.